Tert‐Butylcarbamate‐Containing Histone Deacetylase Inhibitors: Apoptosis Induction, Cytodifferentiation, and Antiproliferative Activities in Cancer Cells. Issue 5 (25th March 2013) - Valente, Sergio; Trisciuoglio, Daniela; Tardugno, Maria; Benedetti, Rosaria; Labella, Donatella; Secci, Daniela; Mercurio, Ciro; Boggio, Roberto; Tomassi, Stefano; Di Maro, Salvatore; Novellino, Ettore; Altucci, Lucia; et al.
Abstract Herein we report novel pyrrole‐ and benzene‐based hydroxamates (8, 10) and 2′‐aminoanilides (9, 11) bearing the tert‐butylcarbamate group at the CAP moiety as histone deacetylase (HDAC) inhibitors. Compounds 8 b and 10 c selectively inhibited HDAC6 at the nanomolar level, whereas the other hydroxamates effected an increase in acetyl‐α‐tubulin levels in human acute myeloid leukemia U937 cells. In the same cell line, compounds 8 b and 10 c elicited 18.4 and 21.4 % apoptosis, respectively (SAHA: 16.9 %), and the pyrrole anilide 9 c displayed the highest cytodifferentiating effect (90.9 %). In tests against a wide range of various cancer cell lines to determine its antiproliferative effects, compound 10 c exhibited growth inhibition from sub‐micromolar (neuroblastoma LAN‐5 and SH‐SY5Y cells, chronic myeloid leukemia K562 cells) to low‐micromolar (lung H1299 and A549, colon HCT116 and HT29 cancer cells) concentrations. In HT29 cells, 10 c increased histone H3 acetylation, and decreased the colony‐forming potential of the cancer cells by up to 60 %.